Pengaruh Lingkungan Belajar Dan Perhatian Orang Tua Terhadap Prestasi Belajar Siswa Kelas Tinggi SD Muhammadiyah Baturan ColomaduTahun Ajaran 2015/2016 - Sukma, Bima Pernama; , Dra. Risminawati, M.Pd (2016)
This study aims to know: (1) Is there any influence of the learning environment on student achievement of high grade SD Muhammadiyah Baturan. (2) Is there any influence of parents' attention on student achievement of high grade SD Muhammadiyah Baturan. (3) Is there any influence of the learning environment and parents' attention on student achievement of high grade SD Muhammadiyah Baturan. The method used is descriptive quantitative research. The population in this study were all students of the high grade (grade IV, V, VI SD Muhammadiyah Baturan Colomadu Academic Year 2015/2016) totaling 59 students. Based on the results of multiple linear regression analysis obtained by the following equation: Y = 15,449+ 0,623X1 + 0,276X2. The results of the data analysis significance level of 5% was obtained: (1) There is the influence of the learning environment on student achievement of high grade SD Muhammadiyah Baturan, the hypothesis can be accepted by t test obtained t> t table (3.881> 2.048) and the significance value <0.05 ( 0.001 <0.05). (2) There is the influence of parents' attention on student achievement of high grade SD Muhammadiyah Baturan, the hypothesis can be accepted by t test obtained t> t table (2.172> 2.048) and the significance value <0.05 (0.039 <0.05). (3) There is the influence of the learning environment and parents' attention on student achievement of high grade SD Muhammadiyah Baturan, the hypothesis can be accepted by the F test obtained F count> F table (67 850> 3.39) and a significant value <0.05 (0.009 <0 , 05). Keywords: learning environment, parents' attention, learning achievement.